Risk Factors for Delayed Extubation after Ventricular Septal Defect Closure: a Prospective Observational Study - Parmar,Divyakant (2017)
Objective: The objective of our study was to determine the feasibility of early extubation and to identify the risk factors for delayed extubation in pediatric patients operated for ventricular septal defect closure. Methods: A prospective, observational study was carried out at our Institute. This study involved consecutive 135 patients undergoing ventricular septal defect closure. Patients were extubated if feasible within six hours after surgery. Based on duration of extubation, patients were divided two groups: Group 1= extubation time ≤ 6 hours, Group 2= extubation time >6 hours. Results: A total of 99 patients were in Group 1 and 36 patients in Group 2. Duration of ventilation was 4.4±0.9 hours in Group 1 and 25.9±24.9 hours in Group 2 (P<0.001). Univariate analysis showed that young age, low weight, low partial pressure of oxygen, trisomy 21, multiple ventricular septal defect, high vasoactive inotropic score, transient heart block and low cardiac output syndrome were associated with delayed extubation. However, regression analysis revealed that only trisomy 21 (OR: 0.248; 95%CI: 0.176-0.701; P=0.001), low cardiac output syndrome (OR: 0.291; 95%CI: 0.267-0.979; P=0.001), multiple ventricular septal defect (OR: 0.243; 95%CI: 0.147-0.606; P=0.002) and vasoactive inotropic score (OR: 0.174 95%CI: 0.002-0.062; P=0.039) are strongest predictors for delayed extubation. Conclusion: Trisomy 21, low cardiac output syndrome, multiple ventricular septal defect and high vasoactive inotropic score are significant risk factors for delay in extubation. Age, weight, pulmonary artery hypertension, size of ventricular septal defect, aortic cross-clamp and cardiopulmonary bypass time did not affect early extubation.